Exploring EFL Students’ Perceptions and Learning Experiences in Utilizing Smalltalk2me Media in Enhancing Speaking Skills - Hamdi, Muhamad Zulpiani; Annuri, Nur Hairunnisa; Putri, Jingga Sulistia; Muawanah, Siti; Alfin, Rahmat; Ariawan, Soni; Suhandra, Ika Rama; Lee, Dong Bae; Rahmat, Heri (JOLLT Journal of Languages and Language Teaching, 2026)
This study investigates EFL students’ perceptions and learning experiences in using SmallTalk2Me, an AI powered speaking platform, to support speaking development. Employing a descriptive qualitative design, the study involved ten students from the English Education Study Program at the State Islamic University of Mataram, selected through purposive sampling. Data were collected through classroom observation during a mini workshop and semi structured interviews. The findings reveal that students generally perceived SmallTalk2Me positively because it provided immediate and useful feedback on fluency, pronunciation, grammar, and vocabulary. Contextualized prompts, interactive features, and CEFR based evaluations increased learners’ confidence, motivation, and willingness to speak more spontaneously. Participants also appreciated the platform’s natural conversational practice and its support for self directed learning. However, several challenges emerged, including limited access to free features, unstable internet connections, difficulty understanding some features, and a lack of topic variety, especially for beginners. Students suggested expanding conversation topics, providing more detailed corrective feedback, and making premium services more affordable. Overall, SmallTalk2Me shows strong potential as an adaptive medium for enhancing EFL speaking practice, although further development is needed to improve accessibility, inclusivity, and effectiveness in broader instructional contexts.